Views of village development and security committee toward sustainable rural development - Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Othman, Jamilah; Tamam, Ezhar; Hamsan, Hanina Halimatusaadiah (Friends Science Publishers, 2010)
This study was conducted to identify the perception of rural administrators, which is Village Development and Security Committee towards sustainable level of Vision Village Movement Village. This study also keens to know factors that affect it. A total of 235 respondents from three states (Selangor, Pahang & Negeri Sembilan) were involved. Data collection process for this study had been conducted for two months. Overall, the respondents highly perceived their village sustainable development. From the Pearson Correlation employed it can be concluded that age and period of staying in the VVM village had significant and positive relationship with perception towards sustainable level.